An Interesting Autopsy case Report of Acute Respiratory Failure (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Introduction Acute respiratory distress comes with a lot of etiological factors. The least common amongit is, diffuse alveolar hemorrhage which constitutes more than 50 of the mortality rate. One of the leastcommon cause of diffuse alveolar hemorrhage is Small vessel vasculitis. Vasculitis is a group of rare butpotentially serious disorders characterized by inflammation of blood vessels.Clinical profile Vasculitis presents with multiple etiological factors, but it is believed to involve anabnormal immune response. The immune system mistakenly attacks healthy blood vessels, leading toinflammation. Some cases of vasculitis are linked to autoimmune disorders, where the body's immunesystem attacks its tissues. Other possible triggers include infections, certain medications, and exposureto toxins.The affected individual presents with fatigue, muscle pain, fever, cough, hemoptysis ,abdominal pain, blood in urine or weakness and numbness in hands or feet. In severe cases there ispresence of blood and protein in urine , making it appear brownish and foamy , high blood pressure andrespiratory problemResults Diagnosing vasculitis can be complex, as its symptoms often overlap with other medicalconditions. The prognosis is extremely poor if not diagnosed in time. Hence better clinical history andadequate tests like test for ANCA antibodies, LFT and KFT is extremely important. Treatment forvasculitis aims to control inflammation, alleviate symptoms, and prevent further damage to organs. Theapproach often involves administration of corticosteroids, immunosuppressants, biological therapies,plasmapheresis and supportive careDiscussion A 29 year old serving soldier was admitted with complains of fever, pain abdomen,hemoptysis, bodyache and dark coloured urine since 03 days. On admission patient was tachypneic andhypotensive. Blood investigations revealed decrease hemoglobin and platelet count. pANCA came out tobe positive. Despite management with oxygenation, iv fluids and iv antibiotics, there was noimprovement in his symptoms and his condition further deteriorated. Bronchoscopy revealed diffusebronchoalveolar hemorrhage. Biochemical evaluation revealed deranged kidney and liver function test.Patient on ventilation developed bradycardia, hypotension and desaturation. On examination bloodpressure was not recordable, carotid pulse was not recordable, CPR was started and patient wasdeclared dead at 1215hrs on 30 Oct 2020.Conclusion Vasculitis is a rare autoimmune disorder and hence its diagnosis is extremely challenging.There is no god standard or clinical criteria to diagnose a case of vasculitis. Hence early diagnosis andmedical intervention is extremely important to improve long term survival.